What's New in Windows Vista? - Culp, Brian (O'Reilly short cuts., 2006)
Get ready for a quick blast through this significant change to Windows! This guide will give you a quick look at many of the most significant new features in Vista, Microsoft's first revision of Windows in nearly six years.